2022
DOI: 10.1021/acsaem.2c00506
|View full text |Cite
|
Sign up to set email alerts
|

Defect Passivation and Fermi Level Modification for >10% Evaporated All-Inorganic CsPbBr3 Perovskite Solar Cells

Abstract: Current CsPbBr 3 perovskite solar cells still suffer from a high open-circuit voltage (V oc ) loss due to the high defect density. Herein, we demonstrate a strategy to passivate defects and induce Fermi level modification through BaI 2 doping. The carrier lifetime is significantly extended after adding BaI 2 . In addition, the Fermi level is changed as Ba 2+ enters the crystal lattice, which increases the built-in potential and promotes the transport of carriers. As a result, the optimized thermally evaporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…3(c)) was found in airprocessed CPIB and 0.8 mg PEAI-assisted CPIB films. Various studies showed the XPS of pristine inorganic CsPbI 2 Br (CPIB)/ CsPbBr 3 /CsPbIBr 2 perovskites that consisted of the C 1s adventitious carbon peak, [47][48][49][50][51] which might be due to the deposition of a tiny layer carbonaceous material on the surface when exposed to film under an air atmosphere. [52][53][54] For instance, Liang et al found the adventitious carbon C 1s peak in the XPS spectrum of inorganic CsPb 0.9 Sn 0.1 IBr 2 perovskite film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(c)) was found in airprocessed CPIB and 0.8 mg PEAI-assisted CPIB films. Various studies showed the XPS of pristine inorganic CsPbI 2 Br (CPIB)/ CsPbBr 3 /CsPbIBr 2 perovskites that consisted of the C 1s adventitious carbon peak, [47][48][49][50][51] which might be due to the deposition of a tiny layer carbonaceous material on the surface when exposed to film under an air atmosphere. [52][53][54] For instance, Liang et al found the adventitious carbon C 1s peak in the XPS spectrum of inorganic CsPb 0.9 Sn 0.1 IBr 2 perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…47 The adventitious carbon C 1s peak was used to calibrate the XPS data. 49 The high-resolution C 1s peak spectrum for CPIB and 0.8 mg PEAI CPIB films is provided in Fig. S6.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, two time constants (τ 1 , τ 2 ) can be calculated and summarized in Table S3. The fast competent (τ 1 ) can be assigned to the surface defect-related recombination and the slow competent (τ 2 ) was due to the band-to-band bulk recombination. , According to Table S3, the average time constant (τ ave ) has increased from 4.46 ns (control) to 8.73 ns (SbI 3 passivated devices). More interestingly, the proportion of the fast process (A 1 ) has reduced to 28.21% of SbI 3 -passivated devices, pointing to reduced surface recombination.…”
Section: Resultsmentioning
confidence: 99%
“…[33] Finally, the all-inorganic CsPbBr 3 PSC free of a hole transporting material and noble metal electrode with the architecture of FTO/c-TiO 2 /m-TiO 2 /CsPbBr 3 /carbon achieves a PCE of 8.94% under one standard sun irradiation (100 mW cm À2 , air mass 1.5) (Figure S1c-e, Supporting Information), in which the thicknesses of different components are 200 nm, 400 nm, and 10 μm for TiO 2 layer, CsPbBr 3 layer, and carbon electrode, respectively, which is comparable to previous reports. [26][27][28][29]36,37] However, the wide bandgap of 2.3 eV leads to a narrow light absorbance below 540 nm and a sluggish efficiency compared to I-containing devices. [38] Therefore, the unabsorbed incident light through the perovskite film will be fully reabsorbed by carbon electrode to convert into heat energy owing to the high absorbance (Figure S2, Supporting Information) and thermal conductivity of carbonaceous materials, which will be discussed in the following part.…”
Section: Resultsmentioning
confidence: 99%
“…[24,25] To the best of our knowledge, all-brominated CsPbBr 3 gives the champion stability among various all-inorganic perovskite materials, enabling a great potential use in CPV. [26][27][28][29] Generally, the state-of-the-art carbon-based, all-inorganic CsPbBr 3 PSCs can only absorb light with λ < 540 nm for photoexcitation owing to the wide bandgap of %2.3 eV, leaving residual light to be converted into heat. In this fashion, the combination of thermoelectric generators (TEGs) with carbon-based PV systems is regarded as an effective strategy to harvest the waste heat and realize the enhanced electricity output by theoretical and experimental studies.…”
mentioning
confidence: 99%